2013
DOI: 10.1136/jnnp-2012-304864
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis is not linked to multiple sclerosis in a population based study

Abstract: Provenance and peer review Not commissioned; externally peer reviewed. To cite van Doormaal PTC, Gallo A, van Rheenen W, et al. J Neurol Neurosurg Psychiatry 2013;84:940-941. 2013 84: 940-941 originally published J Neurol Neurosurg Psychiatry http://jnnp.bmj.com/content/84/8/940 Updated information and services can be found at: These include: References #BIBL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…However, these results generally support the findings of previous smaller studies examining individual diseases in ALS patients [e.g 1, 2, 6, 20…”
Section: Discussionsupporting
confidence: 91%
“…However, these results generally support the findings of previous smaller studies examining individual diseases in ALS patients [e.g 1, 2, 6, 20…”
Section: Discussionsupporting
confidence: 91%
“…17 A population-based study of 810 ALS cases observed only 2 with a prior diagnosis of MS, which was believed to be no more than expected by chance, and neither had a C9orf72 GGGGCC repeat expansion. 18 This latter result would suggest that our findings in relation to MS and ALS may also be confounded by misdiagnosis.…”
mentioning
confidence: 77%
“…Hence, C9orf72 variation does not appear to be a risk factor for MS. It has been suggested that MS can act as a modifier that increases the likelihood of C9orf72 expansions becoming penetrant and causing concurrent ALS (25), although further investigation is required (40).…”
Section: Discussionmentioning
confidence: 99%